Morphological characteristics and growthof red anchovy larva (Encrasicholina punctifer Fowler, 1938) - Quang, Vo Van (Academia Journal of Biology, 2013)
This paper presented morphological characters and development of red anchovy (Encrasicholina punctifer) larvae collected in the sea waters of Khanh Hoa to Binh Thuan, Vietnam and combined with fish larvae that were reared from wild eggs in laboratory experiment. Based on morphological patterns fish larvae  are classified into four stages of development. Prelarval: the larva hatch, the newly hatched larvae were large yolk, the heart pulsating, eyes not pigmented, segmented body with muscle and wide finwebbing. Larvae: they absorbed yolk sac from 10-13 hours after hatching, the intestine observed clearly, 1-3 hours after the end of yolk absorption, the eyes pigmented. Abdominal margin with two black pigmented rows and pectoral fins large; mouth open and the intestines splitandcorrugated in rewards. It was observed clearly the germ of raysare developed. Postlarvae: they fully formed caudal fin rays, dorsal and anal fins, which formed a number of fin rays. Juveniles basically similar to maturefish; fins complete, along the pigment was formed clusters in size range 30mm, the black pigmented patches formed clearly along both sides of lateral and abdominal cavity; the vertebrate are more stellate pigment; body pigment type as adult fish. The length of newly hatched larvae from 2.00 to 2.80 mm (2.42 mm on average), yolk length from 0.80 to 1.07 mm (1.02 mm on average). After the fish absorbed yolk sac, its length increases longer, the death rate also was high after the absorbed yolk sac. The possitive linear regression is recorded between body standard length and otolith radius. Fish larvae of the groups 20.0 to 22.5 mm in length with an average age of 26 days, and of groups 22.5-25 mm in length : 28.64 days. The sub increment occurs at 10-day post hatch and can be confused for analyzing age. The recruitment of anchovy populations was from 1 to 1.5 month age, consistent with the actual investigation of seasonal spawning and fishing.